Lithium ion battery
By using isothiocyanate additives in lithium-ion batteries and adjusting the structural parameters of the negative electrode sheet, the problem of degradation of battery performance at cycling and high temperatures is solved, and the battery's long life and high power performance are achieved.
Patent Information
- Application Number
- CN202411950868.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Lithium-ion batteries are prone to electrolyte oxidation and decomposition of metal ions and dissolution of metal ions during circulation and high-temperature storage, resulting in a degradation of battery performance.
By adding an appropriate amount of isothiocyanate additive to the electrolyte and adjusting the porosity and adhesion of the negative electrode active layer in the negative electrode sheet, the specific relationship between the electrolyte solution and the negative electrode sheet is satisfied to reduce the interface impedance and improve the lithium ion transmission rate.
It realizes the long life and high power performance of lithium-ion batteries, reduces the interface impedance between the negative electrode sheet and the electrolyte, improves the lithium-ion transmission rate, and improves the dynamic performance of the battery.
Smart Images

Figure BDA0005214837540000011 
Figure BDA0005214837540000021 
Figure BDA0005214837540000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields due to their advantages such as high specific energy, fast charging and discharging capabilities and low self-discharge.
[0003] The oxidative decomposition of electrolyte in lithium-ion batteries will deteriorate battery performance, and the dissolution of metal ions is often accompanied during the cycle and high-temperature storage process, resulting in a decrease in battery performance. As the market demand for lithium-ion batteries continues to grow, higher requirements are placed on the comprehensive performance of batteries. The use of additives is one of the effective ways to improve the comprehensive performance of lithium-ion batteries. Studies have shown that the presence of isocyanate-based additives can eliminate trace amounts of HF and H in the battery. 2 O, reduce the decomposition of the electrolyte, improve battery performance, and isothiocyanate additives will also be reduced at the negative electrode to form polythioamide, which is resistant to high temperature and has low impedance. However, after its addition, it will cause large gas production inside the battery. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a lithium-ion battery with long life and high power performance.
[0005] The present invention provides a lithium ion battery, comprising an electrolyte and a negative electrode plate;
[0006] The electrolyte includes an isothiocyanate additive represented by formula (I);
[0007]
[0008] Wherein M is selected from C1-C10 alkyl or C1-C10 fluoroalkyl;
[0009] The mass content of the isothiocyanate additive represented by formula (I) in the electrolyte is a%;
[0010] The negative electrode plate comprises a negative electrode current collector and a negative electrode active layer;
[0011] The porosity of the negative electrode active layer is c%; the adhesion between the negative electrode active layer and the negative electrode current collector is bN / m;
[0012] The electrolyte and the negative electrode plate satisfy the relationship: 0.2≤100×a×b / c≤120.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] The present invention reduces the interface impedance between the negative electrode sheet and the electrolyte while increasing the lithium ion transmission rate and improving the overall kinetic performance by comprehensively controlling the content of isothiocyanate additives in the electrolyte, the porosity and adhesion of the negative electrode active layer in the negative electrode sheet, while avoiding separation of the negative electrode active material layer and the current collector. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is the mass spectrum of the isothiocyanate additive represented by formula (5) used in the embodiment of the present invention. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0017] The present invention provides a lithium ion battery, comprising an electrolyte and a negative electrode plate; the electrolyte comprises an isothiocyanate additive represented by formula (I);
[0018]
[0019] Wherein M is a C1-C10 alkyl group or a C1-C10 fluoroalkyl group;
[0020] The content of the isothiocyanate additive represented by formula (I) in the electrolyte is a%; the negative electrode plate includes a negative electrode collector and a negative electrode active layer; the porosity of the negative electrode active layer is c%; the adhesion between the negative electrode active layer and the negative electrode collector is b N / m; the electrolyte and the negative electrode plate satisfy the relationship: 0.2≤100a×b / c≤100.
[0021] In the present invention, the adhesion between the negative electrode active layer and the negative electrode current collector can be adjusted by the content and type of the negative electrode binder in the negative electrode active layer. Adhesion refers to the binding force between the active material layer and the current collector, which affects the electron transfer between the current collector and the active material layer. If the adhesion is too small, the electron transfer between the current collector and the active material layer is poor, and the impedance increases. In addition, it will also cause the active material layer and the current collector to fall off easily; if the adhesion is too large, it means that more binder needs to be added, which affects the lithium ion transfer and leads to a low lithium ion transfer rate. In the present invention, the adhesion between the negative electrode active layer and the negative electrode current collector is b N / m; the b is preferably 5 to 50, more preferably 10 to 45, more preferably 10 to 40, and most preferably 10 to 30; in some embodiments provided by the present invention, the b is specifically 30, 12, 28.8, 35, 5.1, 29.4, 48.5, 10.5, 33, 10 or 30.
[0022] Porosity refers to the percentage of void volume in the negative electrode of the battery to the total volume. Appropriate porosity helps to improve the energy density of the battery because the pores can accommodate more electrolytes, allowing ions to be transmitted more smoothly during the charge and discharge process, thereby improving the fast charging performance of the battery. At the same time, the porosity can also affect the cycle life of the battery. However, excessively high porosity may lead to a loose structure of the electrode, reduce the mechanical strength of the battery, and also cause poor electron transmission between particles, increase contact impedance, and thus increase electron transmission impedance; while too low porosity affects lithium ion transmission, thereby affecting the fast charging performance of the battery. According to the present invention, the porosity of the negative electrode active layer is c%; the c% is preferably 10% to 40%, more preferably 12% to 35%; in some embodiments provided by the present invention, the c% is specifically 35%, 12%, 24%, 40%, 35.5%, 26%, 60%, 33%, 27.5% or 30%. In addition, the present invention does not limit the method for adjusting the porosity. Specifically, the porosity can be adjusted by the compaction density of the negative electrode sheet.
[0023] According to the present invention, the electrolyte includes an isothiocyanate additive as shown in formula (I); the isothiocyanate additive is used as a film-forming additive to form a solid electrolyte interface film (SEI film) at the negative electrode parameters. The SEI film formed has good high temperature resistance and low impedance. In the formula (I), M is preferably a C1-C8 alkyl group or a C1-C8 fluoroalkyl group, more preferably a C1-C6 alkyl group or a C1-C6 fluoroalkyl group, and more preferably a C1-C4 alkyl group or a C1-C4 fluoroalkyl group; the number of fluorine atoms in the fluoroalkyl group can be one or more, and there is no special restriction. Fluorination can increase the wettability of the electrolyte, and other halogen substitutions will deteriorate the electrical performance of the battery; in the present invention, most preferably, M is a fluoromethyl group, a fluoroethyl group, a fluoropropyl group, a fluorobutyl group, a methyl group, an ethyl group, a propyl group or a butyl group.
[0024] In a specific embodiment provided by the present invention, the isothiocyanate additive is selected from one or more of formula (1) to formula (16):
[0025]
[0026]
[0027] According to the present invention, the content of the isothiocyanate additive represented by formula (I) in the electrolyte is a%. The isothiocyanate additive can generate polythioamide on the surface of the negative electrode, which is resistant to high temperature and has good stability. However, the amount added cannot be too little. If the amount added is too little, it cannot play a role in reducing the interface impedance and forming a stable SEI film. The amount added cannot be too much. The isothiocyanate additive has a serious gas generation problem because a large amount of gas (hydrogen sulfide) is generated when the isothiocyanate is electrochemically reduced to form SEI at the negative electrode. In the present invention, the a% is preferably 0.01% to 1.5%, more preferably 0.05% to 1.2%, and more preferably 0.1% to 1.0%. In some embodiments provided by the present invention, the a% is specifically 1%, 0.1%, 0.5%, 1.2%, 0.015%, 1.48%, 0.18%, 1.3% or 0.2%.
[0028] The present invention reduces the interfacial impedance between the negative electrode sheet and the electrolyte by comprehensively controlling the content of isothiocyanate additives in the electrolyte, the porosity and adhesion of the negative electrode active layer in the negative electrode sheet, and avoiding the separation of the negative electrode active material layer and the current collector, while increasing the lithium ion transmission rate, thereby improving the overall kinetic performance. In the present invention, the electrolyte and the negative electrode sheet preferably satisfy the relationship of 5≤100×a×b / c≤100, more preferably satisfy the relationship of 10≤100×a×b / c≤100, more preferably satisfy the relationship of 10≤100×a×b / c≤90, more preferably satisfy the relationship of 25≤100×a×b / c≤76, and most preferably satisfy the relationship of 25≤100×a×b / c≤60. In some embodiments provided by the present invention, the 85.71, 10, 60.00, 105, 0.22, 113.08, 119.63, 5.73, 120, 3.33, 60 or 85.71.
[0029] In a specific embodiment provided by the present invention, the electrolyte further includes an unsaturated ester additive; the unsaturated ester additive is preferably one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), allyl ethyl carbonate (AEC), vinyl acetate (VA) and catechol carbonate (CC); the content of the unsaturated ester additive in the electrolyte is d%, preferably 0.5≤d≤3, more preferably 0.5≤d≤2.5, and even more preferably 0.8≤d≤2.5; further specifically, 0.2≤a / d≤2; further specifically, 0.5≤a+d≤4; in some embodiments provided by the present invention, The a / d is specifically 1, 0.1, 0.5, 1.2, 0.3, 1.48, 0.18, 2, 0.17 or 2.5; unsaturated carbonates are combined with isothiocyanate additives to reduce the amount of isothiocyanate additives and improve gas production, because unsaturated carbonates can reduce electrolyte and negative electrode side reactions when the CEI film is initially formed, reduce gas production, and the negative electrode adhesion can be smaller; however, if the unsaturated carbonate is not consumed during the initial film formation, a large amount of gas will be produced during the later cycle. In addition, after the unsaturated carbonate is added, the impedance will also increase. Therefore, the unsaturated carbonate content cannot be too large, the isothiocyanate content cannot be too small, and the negative electrode adhesion cannot be too small. In the present invention, further specifically, when the unsaturated ester additive is included in the electrolyte, the electrolyte and the negative electrode plate preferably satisfy the relationship: 0.5≤100a×b / c≤70. When unsaturated carbonates and isothiocyanates are used in combination, the formula is within the above range to further improve gas production and take into account low impedance. In a specific embodiment provided by the present invention, the unsaturated ester additive is vinylene carbonate (VC). The reason for using VC and isothiocyanate additives in combination: VC can also form an SEI film on the surface of the negative electrode, and VC can achieve better coating of the negative electrode, reduce the side reaction between the negative electrode and the electrolyte, reduce gas production, and improve battery cycle performance, but if the VC content is too high, it will cause excessive impedance and affect the fast charging performance of the battery; the unsaturated ester additives and isothiocyanate additives are used in combination to reduce impedance and avoid excessive addition of isothiocyanates, which causes serious gas production. The ratio is further controlled in the range of 0.2≤a / d≤2, taking into account low impedance and low gas production.
[0030] According to the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active layer; the negative electrode current collector can be a negative electrode current collector well known to those skilled in the art, without any special restrictions, and is preferably copper foil in the present invention; the negative electrode active layer includes a negative electrode active material; the mass concentration of the negative electrode active material in the negative electrode active layer is preferably 90% to 98%; optionally, the mass concentration of the negative electrode active material in the negative electrode active layer is specifically 90%, 92%, 94%, 96%, 97%, 98% or a range between any two of the above values; the negative electrode active material can be a negative electrode active material well known to those skilled in the art, without any special restrictions, and is preferably natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon, silicon, SiO x , silicon carbon or Li 4 Ti 5 O 12 One or more of; In the embodiment provided by the present invention, artificial graphite with a particle size of 9 to 12 μm is used as an example for explanation; the negative electrode active layer also includes a negative electrode conductive agent; the mass concentration of the negative electrode conductive agent in the negative electrode active layer is preferably 0.5% to 5%; optionally, the mass concentration of the negative electrode conductive agent in the negative electrode active layer is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or the range between any two of the above values; the negative electrode conductive agent is a negative electrode conductive agent well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably a conductive agent SP; the negative electrode active layer also includes a negative electrode binder; the mass concentration of the negative electrode binder in the negative electrode active layer is preferably 1% to 5%; optionally, the mass concentration of the negative electrode binder in the negative electrode active layer is 1%, 1.5%, 2%, 2.5% , 3%, 3.5%, 4%, 4.5%, 5% or the range between any two of the above values; the negative electrode binder can be a negative electrode binder well known to those skilled in the art without special restrictions. In the present invention, it is preferably one or more of polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR); the molecular weight of the PAA is preferably 30-100W; optionally, the molecular weight of the PAA is 30W, 40W, 50W, 60W, 70W, 80W, 90W, 100W or the range between any two of the above values; the particle size of the SBR is preferably 120-180nm; optionally, the particle size of the SBR is 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm or the range between any two of the above values.
[0031] According to the present invention, the electrolyte further comprises a solvent; the solvent may be an organic solvent well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably one or more of a carboxylate solvent, a cyclic carbonate and a chain carbonate, and the carboxylate solvent is preferably one or more of methyl acetate, ethyl formate and ethyl acetate; the cyclic carbonate may be a cyclic carbonate well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably ethylene carbonate (EC) and / or propylene carbonate (PC); the chain carbonate may be a chain carbonate well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC); in the embodiments provided by the present invention, EC, EMC are specifically used. Take DEC as the solvent of the electrolyte as an example; the mass of the EC is preferably 20% to 40% of the mass of the electrolyte solvent; optionally, the mass of the EC is 20%, 25%, 30%, 35%, 40% or a range between any two of the above values; the mass of the EMC is preferably 20% to 50% of the mass of the electrolyte solvent; optionally, the mass of the EMC is 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range between any two of the above values; the mass of the DEC is preferably 10% to 40% of the mass of the electrolyte solvent; optionally, the mass of the DEC is 10%, 15%, 20%, 25%, 30%, 35%, 40% or a range between any two of the above values.
[0032] According to the present invention, the electrolyte preferably also includes a lithium salt; the lithium salt is preferably one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium fluorosulfonyl (perfluorobutylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate and lithium tetrafluorooxalatophosphate; the concentration of the lithium salt in the electrolyte is preferably 0.5 to 2 mol / L; optionally, the concentration of the lithium salt in the electrolyte is 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 2 mol / L or a range between any two of the above values.
[0033] According to the present invention, the lithium-ion battery also includes a positive electrode plate; the positive electrode plate includes a positive electrode collector and a positive electrode active layer; the positive electrode active layer includes a positive electrode active material; the mass concentration of the positive electrode active material in the positive electrode active layer is preferably 90% to 98%; optionally, the mass concentration of the positive electrode active material in the positive electrode active layer is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or a range between any two of the above values.
[0034] In a specific embodiment provided by the present invention, the positive electrode active material preferably includes lithium iron phosphate; the particle size of the positive electrode active material is preferably 0.05-10 μm, more preferably 0.1-5 μm, more preferably 0.1-3 μm, and most preferably 0.1-1.5 μm; the negative electrode also has a relatively large impact on the fast charging performance of iron-lithium batteries. After the positive electrode lithium ions reach the negative electrode, they need to be able to quickly reach the inside of the negative electrode active material layer from the negative electrode surface. Therefore, it is necessary to control the porosity and adhesion of the negative electrode to improve fast charging. Therefore, by further controlling the formula range to 0.2≤100×a×b / c≤105, the lithium iron phosphate battery has a higher fast charging performance. To be more specific, the electrolyte and the negative electrode plate preferably satisfy the relationship 0.2≤100×a×b / c≤80, more preferably the relationship 5≤100×a×b / c≤80, further preferably the relationship 10≤100×a×b / c≤80, further preferably the relationship 25≤100×a×b / c≤80, and most preferably the relationship 25≤100×a×b / c≤60.
[0035] In another specific embodiment provided by the present invention, the positive electrode active material includes a ternary positive electrode material; due to the poor structural stability of the ternary positive electrode material, the transition metal ion dissolution is serious, the stability of the SEI film is destroyed, the SEI film is too thick, and the interface impedance increases. By further controlling the formula range within the range of 5≤100×a×b / c≤120, the impedance of the ternary material battery is prevented from being too large; further specifically, the electrolyte and the negative electrode plate preferably satisfy the relationship 5≤100a×b / c≤100, and more preferably satisfy the relationship 10≤100 a×b / c≤100, preferably the relationship 10≤100a×b / c≤90 is satisfied, preferably the relationship 25≤100a×b / c≤76 is satisfied, and most preferably the relationship 25≤100a×b / c≤60 is satisfied; the ternary positive electrode material can be a ternary positive electrode material well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably mainly composed of salts of three elements: nickel, cobalt, and manganese, usually expressed as NCM (nickel cobalt manganese oxide) or NCA (nickel cobalt aluminum oxide); specifically, the structural formula of the ternary positive electrode material is LiNi x Co y Mn z O 2 ; wherein x is greater than or equal to 0.5 and less than 1, y is greater than 0 and less than 0.5, z is greater than 0 and less than 0.5, and x+y+z=1; in the embodiments provided in the present invention, x is specifically 0.6, y is 0.2, and z is 0.2 for illustration.
[0036] According to the present invention, the positive electrode active layer preferably also includes a positive electrode conductive agent and a positive electrode binder; the mass of the positive electrode conductive agent is preferably 0.01% to 3% of the mass of the positive electrode active layer; optionally, the mass of the positive electrode conductive agent is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% of the mass of the positive electrode active layer or a range between any two of the above values; the positive electrode conductive agent is a positive electrode conductive agent well known to those skilled in the art, and there is no special limitation. In the present invention, carbon black and / or carbon nanotubes are preferred; the mass of the positive electrode binder is Preferably, it is 0.01% to 5% of the mass of the positive electrode active layer; optionally, the mass of the positive electrode binder is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% of the mass of the positive electrode active layer or the range between any two of the above values; the positive electrode binder is preferably PVDF; the molecular weight of the PVDF is preferably 60 to 100W; optionally, the molecular weight of the PVDF is 60W, 70W, 80W, 90W, 100W or the range between any two of the above values.
[0037] According to the present invention, the lithium-ion battery further comprises a diaphragm for separating the positive electrode sheet and the negative electrode sheet; the diaphragm is preferably one or more of polypropylene (PP), polyethylene (PE) and polypropylene-phenolic resin composite material.
[0038] The present invention also provides a method for preparing the above lithium ion battery, comprising the following steps:
[0039] S1) Preparation of positive electrode sheet: The positive electrode active material, positive electrode binder and positive electrode conductive agent are mixed evenly and dispersed in NMP to obtain positive electrode slurry; the positive electrode slurry is coated on aluminum foil to obtain a double-sided coated positive electrode sheet; then, the positive electrode sheet is rolled and cut to obtain a positive electrode sheet.
[0040] S2) Preparation of negative electrode sheet: The negative electrode active material, negative electrode conductive agent and negative electrode binder are mixed evenly, and dispersed in deionized water to obtain negative electrode slurry; the negative electrode slurry is coated on copper foil to obtain a double-sided coated electrode sheet; then, the negative electrode sheet is rolled and cut to obtain a negative electrode sheet.
[0041] S3) Preparation of electrolyte: Mixing an organic solvent, a lithium salt and an isothiocyanate additive represented by formula (I) to obtain an electrolyte.
[0042] S4) Assembly and formation: stack the above-mentioned positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain a bare battery cell; place the bare battery cell in an outer packaging shell, inject electrolyte after drying, and obtain a lithium-ion battery through vacuum packaging, standing, formation, shaping and other processes.
[0043] To further illustrate the present invention, a lithium ion battery provided by the present invention is described in detail below in conjunction with an embodiment; the molecular weight of PVDF is about 70W; the molecular weight of PAA is about 60W; the particle size of SBR is 120-180nm; and the particle size of artificial graphite is 9-12μm.
[0044] The reagents used in the following examples are all commercially available.
[0045] Example 1
[0046] 1) Preparation of positive electrode sheet: lithium iron phosphate (particle size of about 1 μm, purchased from Guizhou Anda Technology Energy Co., Ltd.) was used as the main material, and the main material was evenly mixed with the binder PVDF and the conductive agent SP according to 97%:1.2%:1.8%; dispersed in NMP to obtain a positive electrode slurry; the positive electrode slurry was coated on aluminum foil to obtain a double-sided coated positive electrode sheet; then rolled and cut to obtain a positive electrode sheet with a compaction density of 2.5 g / cm 3 .
[0047] 2) Preparation of negative electrode sheet: artificial graphite was mixed evenly with 1.5% conductive agent SP, 1.25% binder PAA and 0.75% binder SBR in a mass ratio of 96.5%, and dispersed in deionized water to obtain negative electrode slurry; the negative electrode slurry was coated on copper foil to obtain a double-sided coated electrode sheet; then roller pressed, and the compaction density was 1.5g / cm 3 , and then cut to obtain the negative electrode sheet.
[0048] 3) Preparation of electrolyte
[0049] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a mass ratio of 3:4:3 to obtain an organic solvent, and then the fully dried lithium salt LiPF 6 The electrolyte was dissolved in the mixed organic solvent to prepare a concentration of 1 mol / L, and then additives A and VC were added at a mass ratio of 1.0%, as shown in Table 1.
[0050] 4) Preparation of isolation membrane
[0051] The coated PP is used as the isolation film, wherein the base film thickness is 7 μm; both surfaces are provided with an aluminum oxide coating, and the coating thickness is 1 μm.
[0052] 5) Assembly, formation, and volume determination
[0053] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, liquid injection, standing, formation, constant capacity and other processes.
[0054] Examples 2 to 15 and Comparative Examples 1 to 2
[0055] The preparation of the lithium-ion battery is the same as that of Example 1, except that the types and amounts of the positive electrode material, negative electrode material, binder and additives are different, as shown in Table 1 and Table 2.
[0056] Figure 1 It is the mass spectrum of the isothiocyanate additive represented by formula (5).
[0057] The performance of the lithium ion batteries obtained in Examples 1 to 9 and Comparative Examples 1 to 2 was tested according to the following method. The test results are shown in Table 1.
[0058] Test method:
[0059] Test method to determine the structure and content of additive A:
[0060] 1) Discharge the battery:
[0061] Use battery charging and discharging equipment to discharge the battery. Discharging conditions: current 0.3C, cut-off voltage 2.5V, record the battery number / barcode;
[0062] 2) Collecting electrolyte:
[0063] In the glove box (H 2 O≤0.1ppm, O 2 ≤0.1ppm) to collect the electrolyte; there are three methods for collecting the electrolyte: after removing the battery cover, ① if there is free electrolyte, use a pipette to collect the electrolyte into a 5mL sample tube, and seal it with sealing glue to prevent leakage of the electrolyte. ② If there is no free electrolyte, use a hydraulic press (Beijing Hengaode Technology Co., Ltd. FY-30 hydraulic press) to continuously pressurize until free electrolyte appears, collect the electrolyte into a sample tube and seal it. ③ Add an appropriate amount of dichloromethane extractant to the battery and record the dichloromethane content. After adding dichloromethane, put the battery into an aluminum-plastic bag and seal it with a heat sealer. Transfer it to an ultrasonic oscillator and oscillate for 12 hours to allow the electrolyte in the electrode to be fully mixed with dichloromethane. Then use a pipette to absorb the mixture of dichloromethane and electrolyte into a 5mL sample tube, and seal the sample tube with sealing glue;
[0064] The collected electrolyte samples were injected into the Agilent Intuvo 9000 gas chromatograph-mass spectrometer for testing using a microinjector to obtain a GC-MS spectrum; the additives VC and additive A were prepared into EMC solutions of different concentrations and respectively injected into the Agilent Intuvo 9000 gas chromatograph-mass spectrometer to obtain a standard GC-MS spectrum of the pure substance, wherein the GC spectrum is a peak area curve corresponding to different concentrations, and the MS curve is a specific spectrum of the substance; the GC-MS spectrum of the electrolyte to be tested was compared with the standard GC-MS spectrum to determine whether the electrolyte to be tested contained additives VC and additive A (for example, if a peak appears in the spectrum of the electrolyte to be tested at the position where the additive VC is located in the standard spectrum, it is determined that the electrolyte to be tested contains VC, and the same applies to other components). Then the content of each component in the electrolyte to be tested is determined based on the peak area of each component.
[0065] Negative electrode adhesion test method:
[0066] Pretreatment process: disassemble the empty battery, take out the negative electrode sheet, soak the negative electrode sheet in dimethyl carbonate (DMC) solution for 2 hours, and dry it at 80°C.
[0067] Take a standard steel plate (50mm×125mm) as the rigid test base plate, and wipe the surface of the steel plate clean with dust-free paper dipped in alcohol. Stick one side of the 50mm×125mm 3M double-sided tape on the steel plate to ensure smooth pasting and no wrinkles; cut the negative electrode sheet with active coating into 50mm×125mm test samples; paste the electrode sheet to be tested on the other adhesive surface of the double-sided tape, and then paste another layer of double-sided tape on the surface of the electrode sheet. During the pasting process, ensure that the contact is smooth and wrinkle-free. After rolling with a roller, use the universal testing machine to clamp the steel plate at one end of the tensile clamp and the 3M tape at the other end. Set the tensile machine stroke to 100mm, and perform the tensile test at a speed of 300mm / min. Set the tensile machine stroke to 100m, record the curve in the tensile machine software diagram and stop the machine when the displacement is greater than 80mm. Read the average tensile force value of the flat part of the curve as the adhesion.
[0068] Test method for the porosity of the negative electrode active layer:
[0069] The porosity ε of the negative electrode active material layer is obtained by the mass difference method. The electrode sheet is cut into a disc with a radius r of 0.95 cm using an electrode sheet punching machine, and the thickness of the electrode sheet and the current collector are measured by a thickness gauge as L and L respectively. 0 , calculate the volume of the negative electrode active material on the cut electrode sheet V = π × r 2 ×(LL 0 );Use a balance with an accuracy of 0.00001g to weigh the mass of the cut electrode and record it as m 1Soak the electrode in hexadecane for 1 hour (completely immersed in it), take out the electrode with tweezers, and dry it with filter paper until the mass is constant, and weigh its mass with a balance and record it as m 2 , substitute the experimental data into the formula: ε=(m 2 -m 1 ) / (V×ρ 0 )×100%, where ρ 0 The density of hexadecane is 0.7734 g / cm 3 , and obtain the electrode porosity ε.
[0070] Fast charging performance test method:
[0071] The battery charging and discharging equipment discharges the battery, and the discharge conditions are as follows: for the positive electrode active material using lithium iron phosphate: charge at a constant current of 0.33C to an upper limit voltage of 3.65V, charge at a constant voltage to a current less than or equal to 0.05C, and then discharge at 0.33C to a lower limit voltage of 2.5V; this is one cycle, charge and discharge for 3 cycles, and the discharge capacity of the third cycle is used as the capacity of the battery; for ternary batteries, charge at a constant current of 0.33C to an upper limit voltage of 4.25V, charge at a constant voltage to a current less than or equal to 0.05C, and then discharge at 0.33C to a lower limit voltage of 2.75V; this is one cycle, charge and discharge for 3 cycles, and the discharge capacity of the third cycle is used as the capacity of the battery. Then after charging to 5% SOC at 0.33C (that is, 5% of the discharge capacity in the third cycle), a fast charging test was performed, specifically: charging to 10% SOC at 1.5C, recording the charging time at this stage as t1, charging to 20% SOC at 1.5C, recording the charging time at this stage as t2, standing for 5 minutes, charging to 30% SOC at 1.5C, recording the charging time at this stage as t3, standing for 5 minutes, charging to 40% SOC at 1.5C, recording the charging time at this stage as t4, standing for 5 minutes, charging to 50% SOC at 1.5C, recording the charging time at this stage as t5, standing for 5 minutes, then charging to 60% SOC at 1.2C, recording the charging time at this stage as t6, standing for 5 minutes, charging to 70% SOC at 1.2C, recording the charging time at this stage as t7, standing for 5 minutes, charging to 80% SOC at 1.2C, recording the charging time at this stage as t8, standing for 5 minutes. Fast charging time t=t1+t2+t3+t4+t5+t6+t7+t8.
[0072] Gas production test method:
[0073] Discharge - record the battery number and use the battery charging and discharging equipment to discharge the battery. The discharge conditions are: current 0.33C, cut-off voltage 2.5V, and then charge the battery to full capacity according to the following conditions;
[0074] Constant capacity - For the positive electrode active material using lithium iron phosphate, charge at a constant current of 0.33C to an upper limit voltage of 3.65V, charge at a constant voltage until the current is less than or equal to 0.05C, and then discharge at 0.33C to a lower limit voltage of 2.5V; this is a cycle, charge and discharge for 3 cycles, and the discharge capacity of the third cycle is used as the capacity of the battery; For the positive electrode active material using ternary, charge at a constant current of 0.33C to an upper limit voltage of 4.25V, charge at a constant voltage until the current is less than or equal to 0.05C, and then discharge at 0.33C to a lower limit voltage of 2.75V; this is a cycle, charge and discharge for 3 cycles, and the discharge capacity of the third cycle is used as the capacity of the battery;
[0075] Full charge: For positive electrode active materials using lithium iron phosphate: charge at a constant current of 0.33C to an upper limit voltage of 3.65V, and charge at a constant voltage until the current is less than or equal to 0.05C;
[0076] For the positive electrode material using ternary, charge at a constant current of 0.33C to an upper limit voltage of 4.25V, and charge at a constant voltage until the current is less than or equal to 0.05C;
[0077] After full charging, perform a gas production test.
[0078] Gas production test
[0079] Then use the water displacement method to test the volume of the battery, which is recorded as V0. Place the battery in a 60°C oven for a period of time and then take it out. After the battery temperature drops to room temperature, use the water displacement method to test the battery volume again, which is recorded as V1. The gas production of the battery during this storage period is V1-V0, and this value divided by the battery's fixed capacity is the gas production per ampere-hour.
[0080] Drainage method to test battery volume:
[0081] 1) Add an appropriate amount of pure water into the container and use a density meter to test its density and record it;
[0082] 2) Adjust the balance to a level and peel the skin (peeling is performed before each battery cell is tested);
[0083] 3) Immerse the battery body and the tabs in the solution, ensuring that the battery does not touch the container wall. After stabilization, read the value and record it as T;
[0084] 4) Turn off the balance and seal the container to prevent the reagent from evaporating.
[0085] The battery volume is T / ρ 液
[0086] Among them, before storage and after storage, tests are performed respectively to obtain T0 and T1;
[0087] V1-V0=T0 / ρ 液 -T1 / ρ液
[0088] Gas production at 60℃ storage = (V1-V0) / battery capacity
[0089] Table 1 Parameters and performance test results of lithium-ion batteries
[0090]
[0091]
[0092] Table 2 Parameters and performance test results of lithium-ion batteries
[0093]
[0094]
[0095] From the comparison between Examples 1 to 15 and Comparative Examples 1 and 2 in Table 1 and Table 2, it can be seen that when 100×a×b / c satisfies the formula range of 0.2 to 100, the interface impedance between the negative electrode sheet and the electrolyte is reduced, and the lithium ion transfer rate is increased. The batteries all show excellent fast charging performance, and the fast charging performance is less than 26min; the gas production is less than 1.5 equal to Ml / Ah; in Comparative Example 1, when 100×a×b / c is lower than 0.2, the fast charging performance of the battery is poor, and the fast charging time exceeds 30min; and the gas production is greater than 1.5Ml / Ah; in Comparative Example 2, when 100×a×b / c is greater than 120, the gas production inside the battery is large;
[0096] Furthermore, the formula range in Examples 1 to 3 satisfies the preferred range of 0.2 to 105; and when each parameter satisfies the preferred range, the battery has both better fast charging and low gas production, the fast charging time is less than 23 minutes, and the gas production is lower than Ml / Ah.
[0097] Combining 1 to 3 and Example 6, it can be seen that when the formula of iron lithium does not satisfy 0.2 to 105, the gas production of the battery in Example 6 is significantly higher than that in Examples 1 to 3, and the fast charging performance is also significantly inferior to that in Examples 1 to 3;
[0098] In combination with Examples 8, 9 and 10, when the positive electrode active material is a ternary positive electrode material, Example 10 does not meet the further preferred range of 5 to 120, the fast charge is significantly worse than that of Examples 8 and 9, and the gas production is greater than that of Examples 8 and 9;
[0099] Combining Examples 3, 11 and 2, it can be seen that when the content of additive A / VC additive content, that is, the ratio a / d, does not meet the preferred range of 0.2 to 2, the fast charging performance of the battery is slightly worse, and the gas production increases;
[0100] In Example 13, VC was not added, the fast charging performance was worse than that of Example 3, and the gas production increased.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A lithium ion battery, characterized in that: Including electrolyte and negative electrode plate; The electrolyte includes an isothiocyanate additive represented by formula (I); Wherein M is selected from C1-C10 alkyl or C1-C10 fluoroalkyl; The mass content of the isothiocyanate additive represented by formula (I) in the electrolyte is a%; The negative electrode plate comprises a negative electrode current collector and a negative electrode active layer; The porosity of the negative electrode active layer is c%; the adhesion between the negative electrode active layer and the negative electrode current collector is b N / m; The electrolyte and the negative electrode plate satisfy the relationship: 0.2≤100×a×b / c≤120.
2. The lithium-ion battery according to claim 1, characterized in that The M is selected from fluoromethyl, fluoroethyl, fluoropropyl, fluorobutyl, methyl, ethyl, propyl or butyl.
3. The lithium-ion battery according to claim 2, characterized in that: The isothiocyanate additive is selected from one or more of formula (1) to formula (16):
4. The lithium-ion battery according to claim 1, characterized in that: The a% is 0.01% to 1.5%; And / or, b is 5 to 50; And / or, the c% is 10% to 40%.
5. The lithium-ion battery according to claim 1, characterized in that: The a% is 0.1% to 1.0%; And / or, b is 10 to 40; And / or, the c% is 12% to 35%.
6. The lithium-ion battery according to claim 1, characterized in that It also includes a positive electrode plate; the positive electrode plate includes a positive electrode active material; the positive electrode active material includes lithium iron phosphate; the electrolyte and the negative electrode plate satisfy the relationship: 0.2≤100×a×b / c≤105.
7. The lithium-ion battery according to claim 1, characterized in that: It also includes a positive electrode plate; the positive electrode plate includes a positive electrode active material; the positive electrode active material includes a ternary positive electrode material; the electrolyte and the negative electrode plate satisfy the relationship: 5≤100×a×b / c≤100.
8. The lithium-ion battery according to claim 1, characterized in that The electrolyte also includes unsaturated ester additives; the unsaturated ester additives are selected from one or more of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, allyl ethyl carbonate, vinyl acetate and catechol carbonate; the content of the unsaturated ester additives in the electrolyte is d%; 0.5≤d≤3.
9. The lithium-ion battery according to claim 8, characterized in that: 0.2≤a / d≤2.
10. The lithium ion battery according to claim 1, characterized in that: The electrolyte also includes a lithium salt; the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium fluorosulfonyl (perfluorobutylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate and lithium tetrafluorooxalatophosphate.
Citation Information
Patent Citations
Silicon-cyanogen electrolyte additive for high-voltage lithium ion battery, electrolyte and battery
CN111416153A
Electrolyte and lithium battery thereof
CN113644315A
Lithium ion battery non-aqueous electrolyte and lithium ion battery
CN114039094A
Electrolyte and lithium ion battery
CN115411368A
High-energy-density super-low-temperature lithium iron phosphate power battery
CN115483370A